Odpowiedzi

2010-03-14T22:37:21+01:00
A) 2 - 4a, dla a = -5
2-4*(-5)= 2+20=22

b)1½b + ¾, dla b = ½
1½ * ½ + ¾ = ¾ + ¾ = 6/4= 3/2

c) 8c² - 13, dla c = -2
8* (-2)² - 13 = 8* 4 -13= 32-13= 19

d) ⅓ - 2d : 5, dla d = -4
1/3 - 2* (-4) / 5 = 1/3 - (-8/5)= 1/3 + 8/5 = 29/15

e) 0,25(f - 0,5) + 0,2 dla f = 0,5
0,25 *( 0,5 - 0,5) +0,2= 0,25*0 +0,2 = 0+0,2 =0,2
2010-03-14T22:38:15+01:00
A) 2-4*(-5)
2+20=22

b)3/2 *1/2+3/4
3/4 + 3/4= 6/4= 1 2/4

d) 1/3+8;5 = 1/3+ 8/5= 5/15+24/15= 29/15

c)32-13=19

e)o,25 (0.5-0.5)+0.2 = 1,25 - 1,25+0,2=0,2

Najlepsza Odpowiedź!
2010-03-14T23:21:26+01:00
A) 2 - 4a, dla a = -5
2-4*-5=
2-(-20)=
2+20=22

b)1½b + ¾, dla b = ½
1½*½ +¾ =
3/2*½+¾ =
¾+¾ =6/4= 1½

c) 8c² - 13, dla c = -2
8*(-2)² -13=
8*4-13=19

d) e³ + e² + e, dla e = -4
(-4)³+(-4)² + (-4)=
-64+16+(-16) = -64

e) 0,25(f - 0,5) + 0,2 dla f = 0,5
0,25(0,5-0,5)+0,2=
0,25+0,2=0,45